AfCFTA in a Rut – Can the Pan-African Agreement Regain Momentum? - Jonas Böschemeier; Feodora Teti; Jan Cernicky; Gunter Rieck Moncayo (CESifo Forum, 2022)
Existing high tariffs and non-tariff trade barriers on the African continent prevent greater intra-African integration. The Pan-African Free Trade Area (AfCFTA), which has been in force since January 2021, aims to generate sustainable growth through greater trade integration on the continent. However, the chances of the agreement's success are still unclear: while the targeted tariff liberalizations could drastically reduce trade costs, it remains questionable whether they will be implemented as planned – lessons from the past indicate great difficulty. Moreover, complex rules of origin allow protectionism through the back door. The next few years will be decisive for the AfCFTA: if member states succeed in implementing the agreement's measures in a disciplined manner, the result could be an integrated African market; however, our analysis leaves very little optimism as structural issues impose major challenges.
Keywords: 330